Analysis of Customer Decisions in Taking Over Pension Financing - Afni, Maulidza; Maulina, Rina (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to analyze customer decisions in taking over pension financing. This research method uses qualitative research by going directly to the field to search for data and using qualitative descriptive analysis. The results of interviews and observations carried out at BSI KCP Nagan Raya 2 are that customers' decisions in taking over pension financing are margin levels, fast and easy service, various products offered, customers need funds and promotions are regularly carried out by BSI. Based on the research that has been carried out, it can be concluded that what influences the customer's decision is that the customer wants to take over pension financing because the customer needs funds to continue living and also does not ignore other factors because the customer also looks at the service, margin level, etc. Other times, customers decide to take over pension financing. In this research, the researcher feels that the research that has been carried out is still far from perfect, so the researcher hopes that in future research he can be more optimal in conducting research on analyzing customer decisions in taking over pension financing at Bank Syariah Indonesia (BSI) and for Bank Syariah Indonesia (BSI) KCP Nagan Raya 2 to always maintain the long-standing collaboration with customers and be able to add new customers to collaborate with Bank Syariah Indonesia (BSI) KCP Nagan Raya 2.